Characterization and modelling of the abnormal electrophysiological response under beta-adrenergic stimulation in hypertrophic cardiomyopathy. (24th May 2021) - Doste, R; Coppini, R; Bueno-Orovio, A
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation Introduction: Hypertrophic Cardiomyopathy (HCM) is the most common inheritable heart pathology and the main cause of sudden cardiac death in young adults. HCM patients often present an enhanced arrhythmogenicity that can lead to lethal arrhythmias, especially during exercise. Recent studies have shown an abnormal response of HCM myocytes to β-adrenergic stimulation (β-ARS), with prolongation of their action potential duration (APD). The mechanisms underlying this aberrant response to sympathetic stimulation remain unknown. Purpose: To investigate the key ionic mechanisms underlying the HCM abnormal response to β-ARS using human-based experimental and computational methodologies. Methods: Experimental ionic currents, action potential and calcium transient were recorded in human adult cardiomyocytes from control and HCM patients. Isoproterenol (10-7 mol/L) was used to elicit β-ARS. Whole-cell ruptured patch voltage clamp experiments were conducted to characterise L-type calcium and potassium currents, with recordings performed before and after 3 min of drug exposure. The latest models of human ventricular electrophysiology and beta-adrenergic receptor signalling were integrated and calibrated using the human measured data. Simulations under isoproterenol were performed to quantify the effects of β-ARS on the action potential and calcium transient. The role of the main ion currents affected by β-ARS and by HCM remodelling was evaluated. Results: In vitro, isoproterenol shortened APD (-16 ± 3%) in control, while prolonging APD in HCM myocytes (+23 ± 8%). Analysis of the measured data indicated two possible mechanisms contributing to APD prolongation in HCM myocytes. Firstly, a protracted L-type calcium current, presenting slower inactivation kinetics in HCM compared to control. The relative increase of potassium currents under β-ARS was also lower in HCM myocytes. The developed in silico models of β-ARS replicated the behaviour observed in the experimental data, based on slower L-type calcium current inactivation kinetics and a smaller increase of potassium currents in HCM. In absence of β-ARS, simulated HCM cardiomyocytes exhibited prolonged APD compared to control (525 ± 88 vs 281 ± 56 ms, p < 0.001). Under β-ARS, APD in control was reduced (-16.46%), whereas APD was prolonged in HCM (+11.63%). Further analysis showed that the reduction of the potassium currents increment under β-ARS was the main cause of the APD prolongation in HCM myocytes, with L-type calcium inactivation minimally contributing to APD prolongation. Conclusions: In this study we assessed the effects of β-ARS on ion currents and APD in control and HCM myocytes. Our modelling results suggest that the increase of potassium repolarising currents under β-ARS is greatly reduced in HCM cardiomyocytes, being the main mechanism underlying their APD prolongation. This APD prolongation may have severe consequences in HCM patients, increasing the risk of exercise-induced arrhythmias.